Immediate Feedback Improves Career Decision Self-Efficacy and Aspirational Alignment - Berger, Nathan; Hanham, Jose; Stevens, Catherine J.; Holmes, Kathryn (Frontiers in Psychology, 2019)
Misalignment between career and education aspirations has been associated with poorer achievement during adolescence and unstable employment in adulthood. In this study, we evaluated whether a brief in-school intervention improved career decision self-efficacy and aspirational alignment. We sampled 211 teenagers living in disadvantaged areas of Western Sydney, Australia using a quasi-experimental non-equivalent groups design. Students completed pre- and post-questionnaires which measured aspirational alignment and career decision self-efficacy. Students in the intervention condition (n = 102) received automated feedback on the alignment of their career and education aspirations, as well as a career information pamphlet detailing the educational pathways to a range of popular careers. Students in the control condition completed both questionnaires but only received feedback and the pamphlet at the end of the study. The intervention improved alignment of career and education aspirations, as well as increased some dimensions of career decision self-efficacy. Students in the intervention group more frequently identified the correct qualification for their career aspiration in the post-questionnaire (57.9%) compared with the pre-questionnaire (48.1%). Students with misaligned aspirations in the intervention group reported higher self-efficacy for gathering occupational information and selecting goals following the intervention. There were no pre-post differences for students in the control condition. The practical significance of this study is that an easy, low-cost intervention can improve aspirational alignment between career and education aspirations, as well as aspects of career decision self-efficacy.